Factors contributing to HIV and AIDS stigma among young adults - Mokwena, Jabu Patrick (University of Limpopo (Turfloop Campus), 2012)
The aim of the study is to determine factors contributing to HIV and AIDS stigma among young adults at Polokwane municipality in the Capricorn district of Limpopo Province, South Africa. A total number of 325 participants were involved in the survey and five focus groups were involved in the qualitative study. The participants’ ages were between 18 and 25 years. Biographical information entailing 14 items was used. Ten questions were used in five focus groups. For the survey, a nine-item stigma questionnaire was used as an independent variable. Dependent variables were the following scales: HIV knowledge, knowing a person with HIV and AIDS, family communication and perceived HIV and AIDS risk. The quantitative analysis shows that knowledge of HIV and AIDS, acquaintance with People Living with HIV and AIDS (PLWHA), gender and socio-economic status, as well as stigmatisation of people living with HIV and AIDS, significantly influence stigmatisation of PLWHA. On the other hand, knowledge of one’s own status, affiliation to religion, family communication, perceived risk and cultural attachment played a limited role in the stigmatisation of people living with HIV and AIDS. In view of the above findings, efforts need to be made to review programmes that are undertaken to create awareness about HIV and AIDS to improve HIV transmission knowledge. Constant interaction among PLWHA should be encouraged since this serves as a buffer to combat stigmatisation of PLWHA. There is a need for further research on gender, to explore in-depth reasons for stigmatisation of PLWHA, especially from females. Research also needs to be done in future to determine the factors that influence people from a high socio-economic level to stigmatise of PLWHA.
Thesis (Ph.D. (Psychology)) -- University of Limpopo, 2012
Keywords: HIV/ AIDS Stigma; Young adults; 362.1969792; HIV (Virus); AIDS (Disease) -- South Africa; Stigma (Social psychology); Young adults